2014
DOI: 10.14411/eje.2014.028
|View full text |Cite
|
Sign up to set email alerts
|

Aphid honeydew: An arrestant and a contact kairomone for Episyrphus balteatus (Diptera: Syrphidae) larvae and adults

Abstract: Abstract. predator searching efficiency increases in response to a variety of environmental cues associated with its prey. the sugary excretion of aphids (honeydew) has been found to act as a prey-associated cue for many aphid natural enemies. In the present study, the honeydew excreted by Acyrthosiphon pisum (harris) was identified as an arrestant and a contact kairomone for young larvae and adults of a common predatory hoverfly, Episyrphus balteatus (De Geer) (Diptera: Syrphidae). First and second instar lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…We showed that the probability that a dispersing E. balteatus larva will visit a certain plant increases with increasing aphid number. As it is known that hoverfly larvae intensify their search activity in areas where honeydew is present (Leroy et al, 2014), high amounts of honeydew that accumulate on aphid-infested plants and in the vicinity might be an important search cue for E. balteatus larvae. Larger aphid colonies produce more honeydew, which increases the probability that larvae will climb plants that contain high numbers of aphids.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the probability that a dispersing E. balteatus larva will visit a certain plant increases with increasing aphid number. As it is known that hoverfly larvae intensify their search activity in areas where honeydew is present (Leroy et al, 2014), high amounts of honeydew that accumulate on aphid-infested plants and in the vicinity might be an important search cue for E. balteatus larvae. Larger aphid colonies produce more honeydew, which increases the probability that larvae will climb plants that contain high numbers of aphids.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, honeydew can be a poor source for natural enemies . In addition, honeydew may indirectly release herbivores from top‐down control by benefiting hyperparasitoids or intraguild predators, substituting for prey in natural enemy diets, and reducing foraging efficiency by dirtying predators' mouthparts . While the value of honeydew for parasitoids is relatively well‐explored, relatively little is known about honeydew's nutritional benefits to predators other than ants .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the feeding site, though, pear psyllids are covered with considerable quantities of honeydew (https://www7.inra.fr/hyppz/RAVAGEUR/6cacpir.htm). Previous studies have shown that the liquid honeydew might entrap small parasitoids or clot the mouthparts and sense organs of natural enemies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this guild of aphidophagous insects, the hoverfly Episyrphus balteatus De Geer (Diptera: Syrphidae) is frequently encountered at aphid-infested sites in the temperate regions of the Northern Hemisphere (Schneider, 1969;Gilbert, 236 Claire Detrain, Melanie Fichaux andFrançois Verheggen 1986, 2005;Tenhumberg, 1995). Just like aphid-tending ants, hoverfly females use semiochemicals to locate aphid colonies and to oviposit eggs from which aphidophagous larvae hatch (Harmel et al, 2001;Almohamad et al, 2007;Verheggen et al, 2008;Leroy et al, 2014). Therefore, both actors are likely to encounter each other.…”
Section: Introductionmentioning
confidence: 99%